EFFECTIVENESS EVALUATION OF SEARCH IN INFORMATION SYSTEMS WITH CONSOLIDATED INFORMATION - Nych, L. Ya.; Kaminskyj, R. M.; Shakhovska, N. B. (Radio Electronics, Computer Science, Control, 2016)
To evaluate the effectiveness of information retrieval there is proposed to share the found documents on pertinent, relevant and irrelevant. Search Performance is ratio to determine the number of pertinent and relevant documents to the number of irrelevant documents and search engine properties have been submitted by the coefficient. The goal of this paper is to develop integrated criterion of evaluating the effectiveness of information retrieval on the results of the issuance of consolidated information systems. The concept of consolidated informationis given. The method of evaluating the effectiveness of information retrieval is built. It demonstrates the usage of the division found and published documents on pertinent, relevant and irrelevant. There is given integral indicator of the relevance of the document search query that takes into account the negative and positive features. Evaluation of effectiveness presented as the total value of the different components. The experiment was performed on the basis of information search in one or several search machines and information on the various search engines for one set of keywords. The approach to building assessment information retrieval is of practical importance because quantitative values obtained local assessments give grounds to optimize the set of keywords and determine the most appropriate information collection and search engines.